Declining Wages for College-Educated Workers in Mexico : Are Younger or Older Cohorts Hurt the Most? - Campos-Vazquez, Raymundo M.; Lopez-Calva, Luis F.; Lustig, Nora (World Bank, Washington, DC, 2016)
Wage inequality has declined in Mexico since 2000. Using data from Mexican labor surveys for the period between 2000 and 2014, this paper investigates whether the decline was driven by wages declining more sharply for younger or older workers. The analysis finds that the wages of older workers declined and the decline was more pronounced in the older cohort. This would seem to support the hypothesis that older workers' skills have become obsolete.